Politics of Female Identity in Traditional Java through the Prism of Pramoedya A. Toer’s Gadis Pantai - Sofi, Muhammad Jauhari (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2018)
Identity is political rather than natural. It is always influenced by the politics of race, class, gender, religion, education, disability, and so on. This paper examines the complexity of political forces that shape female identity at the beginning of the 20th century Java and the reaction the women show in response to the circumstances where they find themselves, with reference to Pramoedya Ananta Toer’s Gadis Pantai. The novel, which is based on the true story of his own grandmother, portrays the life of a practice wife of priyayi, the hereditary governing class of Java. Using interpretive analysis and close reading of the text, the study argues that feudal and patriarchal circumstances help shape female identity in the 20th century Java. Women are doubly discriminated; they find themselves subject to higher powers, i.e. the powers of the feudal lord and the male. However, throughout the novel, the author displays a brand-new female image different from the socially dominant discourses, an image that has qualities of rebellious fervor to trouble the discriminating social category of identity.